Echoes of Slavery: voices from South Africa's past - LOOS, Jackie; Fresh Identity, Karen van Eden, Angela Briggs (Cape Town : David Philip, 2004)
Summary: Reviews 'Echoes of slavery: voices from South Africa's past', by Jackie Loos; and, 'An unsung heritage: perspectives on slavery', by Alan Mountain. Finds the authors of both books argue that the study of cape slavery has immense contemporary relevance and contend that South Africans are generally ignorant of this chapter of their past.
Includes bibliographical references (pages 153-157) and index.
Adult
Keywords: South Africa; History